2017
DOI: 10.1364/oe.25.024376
|View full text |Cite
|
Sign up to set email alerts
|

Causality and information transfer in simultaneously slow- and fast-light media

Abstract: Abstract:We demonstrate the simultaneous propagation of slow-and fast-light optical pulses in a four-wave mixing scheme using warm potassium vapor. We show that when the system is tuned such that the input probe pulses exhibit slow-light group velocities and the generated pulses propagate with negative group velocities, the information velocity in the medium is nonetheless constrained to propagate at, or less than, c. These results demonstrate that the transfer and copying of information on optical pulses to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The fact that the distortion increases on either side, for both slow and fast light, is in agreement with the view that the mechanism for both advancement and delay is a pulse-reshaping (that is, a re-phasing) phenomenon. We note that even in the case of pulse advancement, the speed of information transfer is limited to the speed of light in vacuum [23].…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The fact that the distortion increases on either side, for both slow and fast light, is in agreement with the view that the mechanism for both advancement and delay is a pulse-reshaping (that is, a re-phasing) phenomenon. We note that even in the case of pulse advancement, the speed of information transfer is limited to the speed of light in vacuum [23].…”
Section: Resultsmentioning
confidence: 91%
“…Here, we show that the enhancement can occur in a nonlinear medium with regions of overlapping absorption and gain, without a modification to the lineshape. We demonstrate this effect using 4WM in warm potassium vapor, which has a smaller ground state hyperfine splitting than rubidium or cesium and generally leads to strong absorption of the probe pulse, even at room temperature [21][22][23]. Because the probe pulse is effectively positioned in the center of the absorption line, rather than on the wing [13,14], the shapes of the 4WM resonances remain symmetric in frequency.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Bigelow et al have observed experimentally subluminal and superluminal light propagation in alexandrite crystal measuring group velocities as slow as 91 m s −1 to as fast as −800 m s −1 [14]. The simultaneous propagation of slow and fast light has been demonstrated in a four-wave mixing scheme [15]. Slow and fast light propagation has been discussed in a defect slab doped with polaritonic materials and nanoparticles [16].…”
Section: Introductionmentioning
confidence: 99%